Prehospital interventions to reduce discomfort caused by immobilization in adult trauma victims: a scoping review protocol - Mota, Mauro; Cunha, Madalena; Santos, Eduardo; Abrantes, Tito; Melo, Filipe; Monteiro, Mariana; Reis Santos, Margarida (Wolters Kluwer, 2022)
Objective: The objective of this review is to identify the level of discomfort caused by immobilization as reported by trauma victims, and to map all the interventions in the prehospital context where they have been implemented and evaluated in order to reduce discomfort in adult victims of trauma. Introduction: Immobilization is a cause of discomfort for trauma victims, which has important implications for the deterioration of vital signs and quality of life. However, discomfort caused by immobilization remains an underexplored topic by the scientific community. Inclusion criteria: This scoping review will consider studies of adult victims of trauma, aged 18 years or over, in prehospital emergency care. Studies that focus on interventions designed to reduce immobilization discomfort, implemented and evaluated by health professionals, of any form, duration, frequency, and dose will be considered. Methods: An initial search of PubMed and CINAHL will be undertaken, followed by a second search for published and unpublished studies without time restrictions, in major health care–related electronic databases. Studies in English, French, Spanish, and Portuguese will be included. Data extraction will be performed independently by 2 reviewers in a tabular format and will include details about the level of discomfort, interventions, populations, study methods, and outcomes of interest. A narrative synthesis will accompany the results and will describe how they relate to the review objectives.
Keywords: Discomfort; Immobilization; Trauma